2009
DOI: 10.1002/da.20650
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of traumatic stress in mothers of children victims of a motor vehicle accident

Abstract: Peritraumatic response and PTSD symptoms should be routinely assessed among parents whose child has experienced a traumatic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
6
22
0
1
Order By: Relevance
“…Thus, only the variable associated with an idiosyncratic assessment of the event appeared to be predictive of the development of a traumatic symptomatology at 6 months. These results also mirror those of Jeavons (2000) and Allenou et al (2010), who had already shown the prominence of the subject's experience (distress felt, fear of dying) in predicting the onset of PTSD and the absence of any effect of the variables linked to the accident (such as severity, being a passenger or the driver or the number of persons involved). In line with the meta-analysis by Ozer et al (2003), our results confirmed the prominence of the peritraumatic variables in the development of PTSD.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, only the variable associated with an idiosyncratic assessment of the event appeared to be predictive of the development of a traumatic symptomatology at 6 months. These results also mirror those of Jeavons (2000) and Allenou et al (2010), who had already shown the prominence of the subject's experience (distress felt, fear of dying) in predicting the onset of PTSD and the absence of any effect of the variables linked to the accident (such as severity, being a passenger or the driver or the number of persons involved). In line with the meta-analysis by Ozer et al (2003), our results confirmed the prominence of the peritraumatic variables in the development of PTSD.…”
Section: Discussionsupporting
confidence: 84%
“…These findings align with other studies to underscore that special attention should be paid to victims of MVC in the trauma care setting with regard to future persistent PTS symptoms. 11,34,35 The relationship between Hispanic ethnicity and a positive STEPP score was notable but also failed to achieve statistical significance ( p = 0.077). However, this finding aligns with some scientific literature regarding elevated risk of PTS among Hispanic individuals.…”
Section: Discussionmentioning
confidence: 75%
“…In line with this, other studies reported that mothers who had been in or SRS-PTSD = self-rating-scale for PTSD SASRQ = stanford acute stress reaction questionnaire had witnessed an accident that involved their child were significantly more likely to have traumatic stress symptoms (Bryant, Mayou, Wiggs, Ehlers, & Stores, 2004;de Vries et al, 1999). Interestingly, although the threat or salience of death may appear critical in the development of traumatic stress disorders in parents, many studies reported no association between objective medical characteristics (such as length of hospital stay, severity of illness, length of ventilatory support, and risk of mortality) and traumatic stress symptomatology in parents (Row 1 of Table 3, Allenou et al, 2010;Row 16, Balluffi et al, 2004;Row 17, Bronner, Knoester, Bos, Last, & Grootenhuis, 2008;Row 23, Landolt, Boehler, Schwager, Schallberger, & Nuessli, 1998;Row 18, Landolt et al, 2002;Row 13, Lefkowitz, Baxt, & Evans, 2010;Row 14, Shaw et al, 2006). This finding is consistent with Kazak's model of medical traumatic stress which contends that it is the subjective appraisal of threat not illness factors that will predict an individual's response to a diagnosis (Kazak et al, 2006).…”
Section: Prevalencementioning
confidence: 94%
“…Whilst the majority of studies examined represented fathers well, three studies included mothers only (Row 1 of Table 2, Allenou et al, 2010;Row 12, Holditch-Davis et al, 2009;Row 15, Vanderbilt, Bushley, Young, & Frank, 2009) and in seven studies the sample comprised significantly more mothers than fathers. The exclusion of fathers is limiting considering recent evidence supporting the importance of fathers in healthcare contexts (Bronner et al, 2008).…”
Section: Prevalencementioning
confidence: 97%